Story Design in Fine Dining Projection Mapping Project “ Si Dulang “ - Yohanes Merci Widiastomo (Universitas Multimedia Nusantara, 2023)
Projection technology is a technology that is familiar to modern society. It has been seen a lot in everyday life, from attending class lectures and watching movies in the theater. Projection technology is also used in creating art, such as projection mapping in various objects. Projection-Mapping is one of the technological achievements that opens complete access for artists to create and tell stories uniquely. Storytelling is something that humans always do over generations. The usage of technology these days is not limited in terms of form. One of the innovative ways to use projection mapping is